PENGEMBANGAN MODEL PEMBELAJARAN PADA MATA PELAJARAN PKN MATERI KEMERDEKAAN MENGELUARKAN PENDAPAT UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMPN 2 GEDANGAN SIDOARJO - Suyono suyono (Buana Pendidikan, 2013)
The purpose of research is to determine whether the development of problem solving models of cooperative learning on learning outcomes Civics class VII student of SMP Negeri 2 Gedangan Sidoarjo. The research model used in this study probling solving learning model is a model of Dick , Carey (2001 ) . Model Dick , Carey and Carey (2001 ) consists of ten steps but in this study the researcher only restricts nine steps . This model leads to efforts to solve the problem in a systematic and programmed learning . The model used in the development of this learning package is a model of problem solving . This model leads to a learning problem-solving efforts in a systematic and educate more independent learners . This is a qualitative development by providing facts and data on the development of teaching materials , and then dianalsis by using percentages . Technique is the analysis of data collected from the questionnaire will be used descriptive statistical analysis . Data from the questionnaires will be analyzed to get an overview of the development of instructional media . Having collected the questionnaire will be considered in the improvement of software that will be used and give advice as well as further research utilization . This analysis technique is used to process the data obtained through the questionnaire in the form of descriptive percentage ( sutrisno , 1995) . each subject .Based on the results of expert assessment of the subject matter content of teaching materials calculation of the percentage 78.53 % , to guide educators 80 % , 100 % of the learners . Based on the results of expert assessment of instructional design instructional materials calculation of the percentage of the 89 % , to guide pendidik100 % , against 92.7 % of learners . Based on the assessment results of individual trials against teaching materials calculation 93.66 % , against 89.22 % guide educators , the learners 82.21 % . Based on the assessment results of field trials of the calculation of the percentage of teaching materials 89.64 % , against 89.09 % guide educators , the learners 89.49 % . Based on the results of expert assessment of the course content , instructional design experts , media experts , Ujin try individuals , and field-testing of the material wrote , educator guides , and guide learners if converted to table the level of achievement of the results have been good .